2017
DOI: 10.3389/fnins.2017.00587
|View full text |Cite
|
Sign up to set email alerts
|

Syndromic Craniosynostosis Can Define New Candidate Genes for Suture Development or Result from the Non-specifc Effects of Pleiotropic Genes: Rasopathies and Chromatinopathies as Examples

Abstract: Craniosynostosis is a heterogeneous condition caused by the premature fusion of cranial sutures, occurring mostly as an isolated anomaly. Pathogenesis of non-syndromic forms of craniosynostosis is largely unknown. In about 15–30% of cases craniosynostosis occurs in association with other physical anomalies and it is referred to as syndromic craniosynostosis. Syndromic forms of craniosynostosis arise from mutations in genes belonging to the Fibroblast Growth Factor Receptor (FGFR) family and the interconnected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 73 publications
2
23
0
Order By: Relevance
“…Findings in 2 patients with large deletions close to TWIST1 suggested that haploinsufficiency of neighboring genes may also contribute to developmental delay in these cases [Johnson et al, 1998]. These observations are in agreement with the notion of a contiguous gene syndrome as a possible genomic cause for complex disorders, which include craniosynostosis as one of its phenotypes, such as Kabuki, 17q21.31 deletion (Koolen-De-Vries/KANSL1 syndrome), and 9p23p22.3 deletion syndrome [Koolen et al, 2008;Sharkey et al, 2009;Dubourg et al, 2011;Koolen et al, 2016;Topa et al, 2017;Zollino et al, 2017].…”
Section: Disruption Of Genes and Network Entailing Dominant And Pleisupporting
confidence: 64%
See 4 more Smart Citations
“…Findings in 2 patients with large deletions close to TWIST1 suggested that haploinsufficiency of neighboring genes may also contribute to developmental delay in these cases [Johnson et al, 1998]. These observations are in agreement with the notion of a contiguous gene syndrome as a possible genomic cause for complex disorders, which include craniosynostosis as one of its phenotypes, such as Kabuki, 17q21.31 deletion (Koolen-De-Vries/KANSL1 syndrome), and 9p23p22.3 deletion syndrome [Koolen et al, 2008;Sharkey et al, 2009;Dubourg et al, 2011;Koolen et al, 2016;Topa et al, 2017;Zollino et al, 2017].…”
Section: Disruption Of Genes and Network Entailing Dominant And Pleisupporting
confidence: 64%
“…Nonsyndromic cases of sagittal and/or metopic craniosynostosis should first be screened for SMAD6 mutations, and nonsyndromic coronal craniosynostosis be investigated for TCF12 and TWIST1 mutations and the FGFR3 P250R variant [Timberlake and Persing, 2018]. Cases of sporadic, nonsyndromic midline craniosynostosis negative for TCF12 and TWIST1 mutations and the FGFR3 P250R variant as well as their parents should preferably be investigated by array-CGH, WES, or WGS [Zollino et al, 2017;Kutkowska-Kaźmierczak et al, 2018;Timberlake and Persing, 2018]. The thus found de novo CNVs and SNVs may then be prioritized for adhering to the GO category of skeletal development (GO:0001501) or the wider category of development (GO:0007275).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations